Two-dimensional position detection system with MEMS accelerometers, readout circuitry, and microprocessor for padless mouse applications. - Seungbae Lee (IEEE Transactions on VLSI systems)
A hybrid two-dimensional position sensing system is designed with microelectromechanical systems (MEMS) for padless mouse applications. The X/Y-axis acceleration of the user's hand movements is measured by two MEMS accelerometer devices. These acceleration values are pulsewidth modulated and converted into (X, Y) coordinates on the screen by integral operations on a microprocessor. The overall system consists of four major components: 1) MEMS accelerometers; 2) CMOS analog readout circuitry; 3) an acceleration magnitude extraction module; and 4) a 16-b RISC microprocessor. Mechanical and analog simulation shows that the designed mouse system can detect acceleration as small as 5.3 mg (g=9.8 m/s2) with 100-kHz sampling frequency for low power consumption.